====== setMandelstam ====== ---- ====Description==== * ''setMandelstam([k1:m1, k2:m2, k3:m3, k4:m4])'' generates a list of Mandelstam and mass shell substitutions for incoming particles with momentums ''k1'' and ''k2'' with masses ''m1'' and ''m2'' and outcoming particles with momentums ''k3'' and ''k4'' with masses ''m3'' and ''m4''. * ''setMandelstam([k1:m1, k2:m2, k3:m3, k4:m4], s, t, u)'' generates a list of Mandelstam substitutions with specified notation for Mandelstam s, t and u variables. * ''setMandelstam'' uses the following definition of Mandelstam variables: \begin{gather*} s = (p_1 + p_2)^2 = (p_3+p_4)^2\\ t = (p_1 - p_3)^2 = (p_2 - p_4)^2\\ u = (p_1 - p_4)^2 = (p_2 - p_3)^2 \end{gather*} ====Examples==== Generate a list of Mandelstam and mass shell substitutions: def mandelstam = setMandelstam([k1_a: 'm1', k2_a: 'm2', k3_a: 'm3', k4_a: 'm4']) println mandelstam > k1_{a}*k1^{a} = m1**2 > k2_{a}*k2^{a} = m2**2 > k3_{a}*k3^{a} = m3**2 > k4_{a}*k4^{a} = m4**2 > 2*k1_{a}*k2^{a} = s-m2**2-m1**2 > 2*k4^{a}*k3_{a} = s-m3**2-m4**2 > -2*k3^{a}*k1_{a} = t-m3**2-m1**2 > -2*k4^{a}*k2_{a} = t-m4**2-m2**2 > -2*k4^{a}*k1_{a} = -m4**2-m1**2+u > -2*k3^{a}*k2_{a} = -m3**2-m2**2+u ---- Same when some particles are massless: def mandelstam = setMandelstam([k1_a: '0', k2_a: 'm2', k3_a: 'm3', k4_a: '0']) println mandelstam > k1_{a}*k1^{a} = 0 > k2_{a}*k2^{a} = m2**2 > k3_{a}*k3^{a} = m3**2 > k4_{a}*k4^{a} = 0 > 2*k2^{a}*k1_{a} = -m2**2+s > 2*k4^{a}*k3_{a} = -m3**2+s > -2*k3^{a}*k1_{a} = -m3**2+t > -2*k4^{a}*k2_{a} = t-m2**2 > -2*k4^{a}*k1_{a} = u > -2*k2_{a}*k3^{a} = -m3**2+u-m2**2 ---- Specify custom notation for Mandelstam variables: def mandelstam = setMandelstam( [k1_a: 'm1', k2_a: 'm2', k3_a: 'm3', k4_a: 'm4'], 'hS', 'hT', 'hU') println mandelstam > k1_{a}*k1^{a} = m1**2 > k2_{a}*k2^{a} = m2**2 > k3_{a}*k3^{a} = m3**2 > k4_{a}*k4^{a} = m4**2 > 2*k2^{a}*k1_{a} = -m1**2+hS-m2**2 > 2*k3_{a}*k4^{a} = -m3**2+hS-m4**2 > -2*k3^{a}*k1_{a} = -m3**2-m1**2+hT > -2*k2_{a}*k4^{a} = hT-m4**2-m2**2 > -2*k1_{a}*k4^{a} = -m1**2+hU-m4**2 > -2*k2_{a}*k3^{a} = -m3**2+hU-m2**2 ====See also==== * Related tutorials: [[documentation:tutorials:compton_scattering_in_scalar_qed]], [[documentation:tutorials:compton_scattering_in_qed]] * Related functions: [[documentation:ref:setmandelstam5]] * JavaDocs: [[http://api.redberry.cc/redberry/1.1.9/java-api/cc/redberry/physics/feyncalc/FeynCalcUtils.html|FeynCalcUtils]] * Source code: [[https://bitbucket.org/redberry/redberry/src/tip/physics/src/main/java/cc/redberry/physics/feyncalc/FeynCalcUtils.java|FeynCalcUtils.java]]